Pancreas transplantation: an overview - David,Andre Ibrahim (2010)
ABSTRACT Pancreas transplantation is the only treatment able to reestablish normal glucose and glycated hemoglobin levels in insulin-dependent diabetic patients without the use of exogenous insulin. The evolution of pancreas transplantation in treatment of diabetes was determined by advances in the fields of surgical technique, organ preservation and immunosuppressants. The main complication leading to graft loss is technical failure followed by acute or chronic rejection. Technical failure means graft loss within the first three months following transplantation due to vascular thrombosis (50%), pancreatitis (20%), infection (18%), fistula (6.5%) and bleeding (2.4%). Immunological complications still affect 30% of patients, and rejection is the cause of graft loss in 10% of cases. Chronic rejection is the most common late complication. Cardiovascular diseases are the most common causes of late mortality in pancreas transplantation, so it remains the most effective treatment for type 1 diabetes patients. There is a significant improvement in quality of life and in patient's survival rates. The development of islet transplantation could eliminate or minimize surgical complications and immunosuppression.